209k views
2 votes
(2x-4)/(x^2-4)+(x-3)/(x^2+5x+6) simplify

User Darklow
by
5.6k points

1 Answer

4 votes

Answer:

3(x + 1)

= ------------------

(x +2)(x + 3)

Explanation:

(2x-4) (x-3)

--------------+ ------------------------

(x^2-4) (x^2+5x+6)

(2x-4) (x-3)

= -------------- ----+ ------------------------

(x + 2)(x - 2) (x + 3)(x + 2)

GCF = (x +2)(x - 2)(x + 3)

(2x - 4)(x + 3) + (x - 3)(x - 2)

= ------------------------------------------

(x +2)(x - 2)(x + 3)

2x^2 + 6x - 4x - 12 + x^2 -2x - 3x + 6

= -----------------------------------------------------------

(x +2)(x - 2)(x + 3)

3x^2 - 3x -6

= --------------------------

(x +2)(x - 2)(x + 3)

3(x^2 - x - 2)

= --------------------------

(x +2)(x - 2)(x + 3)

3(x - 2)(x + 1)

= --------------------------

(x +2)(x - 2)(x + 3)

3(x + 1)

= ------------------

(x +2)(x + 3)

User Pedro Lima
by
5.4k points